2019
DOI: 10.1002/ctpp.201800064
|View full text |Cite
|
Sign up to set email alerts
|

Non‐thermal plasma‐induced apoptosis in yeast Saccharomyces cerevisiae

Abstract: The effect of non‐thermal plasma generated by the direct current (DC) corona discharge in the mode of transition spark is studied on a yeast Saccharomyces cerevisiae. The exposure to plasma increases production of reactive oxygen species (ROS) in cells, possibly causing the induction of apoptosis. To clarify the mechanism of apoptosis, its induction is tested not only on a wild strain of S. cerevisiae, but also on mutant strains: A deletion mutant Δyca1 without yeast metacaspase proves that in S. cerevisiae th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“… Liao et al (2017) have described the mechanisms of microorganism inactivation in detail: the basis of these mechanisms is the damage of nucleic acids by UV radiation, lipid peroxidation caused by ROS occurring mainly in fatty acids near the cell surface, and the chemical modification and degradation of proteins caused mainly by hydroxyl radicals. Other studies also reported apoptosis in bacterial cells probably inducted by ROS ( Čtvrtečková et al, 2019 ). Mechanical cell damage, in particular electrostatic disruption caused by the electrostatic forces of charged particles accumulated on the cells, and electroporation by the direct bombardment of charged particles also applied.…”
Section: Introductionmentioning
confidence: 84%
“… Liao et al (2017) have described the mechanisms of microorganism inactivation in detail: the basis of these mechanisms is the damage of nucleic acids by UV radiation, lipid peroxidation caused by ROS occurring mainly in fatty acids near the cell surface, and the chemical modification and degradation of proteins caused mainly by hydroxyl radicals. Other studies also reported apoptosis in bacterial cells probably inducted by ROS ( Čtvrtečková et al, 2019 ). Mechanical cell damage, in particular electrostatic disruption caused by the electrostatic forces of charged particles accumulated on the cells, and electroporation by the direct bombardment of charged particles also applied.…”
Section: Introductionmentioning
confidence: 84%
“…Although yeast do not have the pathway that directly corresponds to the mammalian apoptotic pathway, it has been generally accepted that yeast cells can undergo regulated cell death and some of the components of yeast cell death pathways are homologous to their mammalian counterparts with well-established roles in apoptosis [ 31 , 32 , 33 , 34 , 35 ]. Interestingly, several changes that are considered as typical hallmarks of regulated cell death have been observed in yeast cells treated with He/O 2 plasma jet [ 36 ] or directly by a corona discharge [ 37 ]. These changes involve generation of a population of cells that are stained with Annexin-V, due to the exposure of phosphatidylserine at the cell surface, while they are not stained with propidium iodide, indicating the intact plasma membrane [ 36 , 37 ]; chromatin condensation that can be visualized by staining with DAPI (4′,6-diamidino-2-phenylindole); decrease in mitochondrial transmembrane potential revealed by staining with TMRM (tetramethylrhodamine methyl ester) and cell cycle arrest in G1 phase [ 36 ].…”
Section: Plasma-induced Cell Death In Yeastmentioning
confidence: 99%
“…Interestingly, several changes that are considered as typical hallmarks of regulated cell death have been observed in yeast cells treated with He/O 2 plasma jet [ 36 ] or directly by a corona discharge [ 37 ]. These changes involve generation of a population of cells that are stained with Annexin-V, due to the exposure of phosphatidylserine at the cell surface, while they are not stained with propidium iodide, indicating the intact plasma membrane [ 36 , 37 ]; chromatin condensation that can be visualized by staining with DAPI (4′,6-diamidino-2-phenylindole); decrease in mitochondrial transmembrane potential revealed by staining with TMRM (tetramethylrhodamine methyl ester) and cell cycle arrest in G1 phase [ 36 ]. These observations may indicate that, at least partially, the dying observed in yeast after the plasma treatment may be attributed to regulated cell death that is triggered as a reaction to, either cell damage or to the presence of reactive particles originating from plasma itself.…”
Section: Plasma-induced Cell Death In Yeastmentioning
confidence: 99%
“…As was described, the exposure of bacteria or yeasts to NTP not only induces direct physical destruction, but also triggers programmed cell death [ 14 ]. Some hallmarks of apoptosis were also found in Pseudomonas aeruginosa [ 15 ] and in yeasts [ 16 ].…”
Section: Introductionmentioning
confidence: 99%